IDENTIFIKASI KANDUNGAN TANNIN DAN SAPONIN HIJAUAN PAKAN SAPI POTONG DI DESA SENAYAN KABUPATEN SUMBAWA BARAT - Apri Sanjani; Mashur; Dina Oktaviana; Novariana SulsiaIsta’in Ningtyas (JURNAL SANGKAREANG MATARAM, 2022)
This study aims to determine the levels of tannin and saponin compounds contained in lamtoro leaves, indigofera leaves and turi leaves used as forage for beef cattle in Senayan Village, Poto Tano District, West Sumbawa Regency. The research method used was laboratory observation using an Ultra Violet-Visible Spectroscopy (UV-VIS) Spectrophotometer at the Integrated Chemistry Laboratory, Faculty of Pharmacy, Stikes Bhakti Husada Mulia Madiun. The results showed that the tannin and saponin levels quantitatively in the three types of forage for beef cattle, namely lamtoro leaf tannins 5.41%, indigofera leaves 7.39% and turi leaves 13.83%. Saponin content of lamtoro leaf is 10.28%, indigofera leaf is 11.82% and turi leaf is 14.55%. Based on these data, it can be concluded that the tannin and saponin levels in turi leaves in this study were higher than indigofera leaves and lamtoro leaves.